Pemanfaatan Pekarangan dan Sampah Organik di Kelurahan Pejarakan Karya - Perdinan Perdinan; Anelia Qonita; Annisa Nur Madani; Muhammad Thufail Mukhairiq; Ridho Rahmatullah Wibowo; Nuzhatun Nazria; Muhammad Faiz Al Anshari; Dhia Adelia Amna; Dewi Agustina Prakusya (Jurnal Pusat Inovasi Masyarakat (PIM), 2021)
One of the health problems in Indonesia today which is also a global pandemic is the spread of Corona Virus Disease 2019 cases. The Indonesian government through Presidential Decree No.11 of 2020 concerning the Determination of Public Health Emergencies for Corona Virus Disease 2019 has stated that COVID-19 is a public health emergency that is prevention efforts must be made. The fairly dense population living in this area can cause the spread of the COVID-19 virus to accelerate if comprehensive prevention efforts are not made. Every individual needs to make efforts to prevent the development and spread of the COVID-19 virus. Actions that can be taken to prevent the spread of COVID-19 in Pejarakan Karya Village are by consuming healthy and nutritious food which is realized by creating a Sustainable Home Yard Socialization (P2L) program and to support the Sustainable Home Yard program a P2L pilot area and fertilizer manufacturing plant have been created. organic liquid made from household waste that can be used by the surrounding community. Keywords: Penjarakan Karya, COVID-19 prevention, yard, liquid organic fertilizer